Experimental colitis in mice is attenuated by changes in the levels of endocannabinoid metabolites induced by selective inhibition of fatty acid amide hydrolase (FAAH). (1st September 2014) - Sałaga, M.; Mokrowiecka, A.; Zakrzewski, P.K.; Cygankiewicz, A.; Leishman, E.; Sobczak, M.; Zatorski, H.; Małecka-Panas, E.; Kordek, R.; Storr, M.; Krajewska, W.M.; Bradshaw, H.B.; et al.
Abstract: Background and aims: Pharmacological treatment and/or maintenance of remission in inflammatory bowel diseases (IBD) is currently one of the biggest challenge in the field of gastroenterology. Available therapies are mostly limited to overcoming the symptoms, but not the cause of the disease. Recently, the endocannabinoid system has been proposed as a novel target in the treatment of IBD. Here we aimed to assess the anti-inflammatory action of the novel fatty acid amide hydrolase (FAAH) inhibitor PF-3845 and its effect on the endocannabinoid and related lipid metabolism during the course of experimental colitis. Methods: We used two models of experimental colitis in mice (TNBS- and DSS-induced) and additionally, we employed LC/MS/MS spectrometry to determine the changes in biolipid levels in the mouse colon during inflammation. Results: We showed that the FAAH inhibitor PF-3845 reduced experimental TNBS-induced colitis in mice and its anti-inflammatory action is associated with altering the levels of selected biolipids (arachidonic and oleic acid derivatives, prostaglandins and biolipids containing glycine in the mouse colon). Conclusions: We show that FAAH is a promising pharmacological target and the FAAH-dependent biolipids play a major role in colitis. Our results highlight and promote therapeutic strategy based on targeting FAAH-dependent metabolic pathways in order to alleviate intestinal inflammation.